Daya Antibakteri Minyak Atsiri Daun Sirih Hijau (Piper betle L.) dan Sirih Merah (Piper Crocatum) Terhadap Bakteri Pseudomonas aeruginosa dan Staphylococcus aureus - Lidwina Ella Septiani; Kianto Atmodjo; B. Boy Rahardjo Sidharta (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Abstract —Betel, have long been known as antibacterial. Based on the shape of the leaves, taste and aroma, betel is divided into several types, but the most widely used are green and red betel leaves. Green and red betel leaves contain phytochemicals such as essential oils compounds such as kavikol, cineol and eugenol. The purpose of this study was to determine the differences in the content of green and red betel leaf essential oil in the old and young treatments and its effectiveness at the concentration used against Staphylococcus aureus and Pseudomonas aeruginosa bacteria. This research begins with the preparation of betel leaf for essential oil distillation, isolation of essential oils by steam-water distillation, analysis of components or compounds of essential oils using GCMS, preparation of pure essential oil stock solutions (100%), preparation of Staphylococcus aureus and Pseudomonas aeruginosa bacteria. then identification test was carried out with several test methods, antibacterial activity testing which began with making variations in concentrations of 10%, 15%, 20%, 25% and 30% with the addition of a positive control of ampicillin disk and a negative control of DMSO with the well diffusion method which was incubated for 24 hours. hours at 37°C. The results of the measurement of the inhibitory zone were analyzed by ANOVA using the factorial RAL pattern, followed by the measurement of the minimum inhibitory concentration (MIC) with a concentration variation of 5%, 10%, 20% and 30% and the determination of the minimum inhibitory concentration (MIC). The results showed that dark green betel leaf essential oil had better antibacterial activity in the inhibition zone test with a concentration of 30% against both bacteria with an inhibitory zone area of ​​1.88 cm for Staphylococcus aureus and 1.21 cm for Psedumonas aeruginosa and the minimum inhibitory concentration test was able to inhibit at a concentration of 10% 10% against Staphylococcus aureus bacteria and at a concentration of 5% on Psedumonas aeruginosa bacteria.